Spatiotemporal Profiling of Starch Biosynthesis and Degradation in the Developing Barley Grain1[W] - Radchuk, V.V; Borisjuk, L.; Sreenivasulu, N.; Merx, K.; Mock, H.P.; Rolletschek, H.; Wobus, U.; Wobus, U.
Barley (Hordeum vulgare)grains synthesize starch as the main storage compound. However, some starch is degraded already during caryopsis development. We studied temporal and spatial expression patterns of genes coding for enzymes of starch synthesis and degradation. These profiles coupled with measurements of selected enzyme activities and metabolites have allowed us to propose a role for starch degradation in maternal and filial tissues of developing grains. Early maternal pericarp functions as a major short-term starch storage tissue, possibly ensuring sink strength of the young caryopsis. Gene expression patterns and enzyme activities suggest two different pathways for starch degradation in maternal tissues. One pathway possibly occurs via a-amylases 1 and 4 and b-amylase 1 in pericarp, nucellus, and nucellar projection, tissues that undergo programmed cell death. Another pathway is deducted for living pericarp and chlorenchyma cells, where transient starch breakdown correlates with expression of chloroplast-localized b-amylases 5, 6, and 7, glucan, water dikinase 1, phosphoglucan, water dikinase, isoamylase 3, and disproportionating enzyme. The suite of genes involved in starch synthesis in filial starchy endosperm is much more complex than in pericarp and involves several endosperm-specific genes. Transient starch turnover occurs in transfer cells, ensuring the maintenance of sink strength in filial tissues and the reallocation of sugars into more proximal regions of the starchy endosperm. Starch is temporally accumulated also in aleurone cells, where it is degraded during the seed filling period, to be replaced by storage proteins and lipids.